Surgical repair of a right coronary aneurysm with a coronary artery fistula to the right atrium. Issue 7 (8th July 2021) - Yokoyama, Shigeki; Nagao, Kanetsugu; Higashida, Akihiko; Aoki, Masaya; Yamashita, Shigeyuki; Yamashita, Akio; Doi, Toshio; Fukahara, Kazuaki; Yoshimura, Naoki
Abstract: A coronary artery fistula is a rare condition caused by abnormal coronary artery embryological development. Although most cases are asymptomatic, in some, the large shunt volume and the myocardial ischemia due to the steal phenomenon require surgical treatment. We present the case of a 40-year-old woman who presented with angina on exertion. Enhanced computed tomography showed a giant right coronary artery (RCA) aneurysm with an RCA-to-right atrium fistula. Because of the presence of symptoms and the presence of large fistulous tract, the patient was considered a surgical candidate. The procedure was performed under cardiopulmonary bypass. Ligation and closure of the fistula were performed in combination with dissection of the enlarged main trunk of the RCA and coronary artery bypass using the internal thoracic artery because of its potential for long-term patency. The postoperative course was uneventful.